2018
DOI: 10.1186/s12935-018-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

C-Phycocyanin exerts anti-cancer effects via the MAPK signaling pathway in MDA-MB-231 cells

Abstract: BackgroundTriple-negative breast cancer is a biological subtype of breast cancer, which is unresponsive to conventional chemotherapies and has a poor prognosis. C-Phycocyanin (C-PC), a marine natural purified from Spirulina platensis, has been investigated that has anti-cancer function. The mitogen activated protein kinase (MAPK) pathway plays a crucial role in the development and progression of cancer. Therefore, we would like to study the anti-cancer effects of C-phycocyanin in the treatment of triple-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 37 publications
1
68
0
Order By: Relevance
“…Activated JNK and ERK1/2 could lead to cell cycle arrest at the G2/M phase [53], which is also witnessed in our study. The role of p38MAPK and MEK1 was diverse in the cancer cells, as they can promote or inhibit cell survival [54]. In the present study, we showed that Lanatoside C at its lethal doses can alter the mechanism of MAPK signaling and inhibits p38MAPK, MEK1, and SAPK/JNK (Figures 4 and 6).…”
Section: Discussionsupporting
confidence: 51%
“…Activated JNK and ERK1/2 could lead to cell cycle arrest at the G2/M phase [53], which is also witnessed in our study. The role of p38MAPK and MEK1 was diverse in the cancer cells, as they can promote or inhibit cell survival [54]. In the present study, we showed that Lanatoside C at its lethal doses can alter the mechanism of MAPK signaling and inhibits p38MAPK, MEK1, and SAPK/JNK (Figures 4 and 6).…”
Section: Discussionsupporting
confidence: 51%
“…p21, a broad-spectrum CDK inhibitor, has been demonstrated to promote cell cycle arrest by inhibiting the activity of various cyclin-CDK complexes [22,23]. Moreover, some studies have suggested that upregulating p21 expression plays an essential role in G0/G1 arrest [24,25]. Wang et al revealed that TA I inhibited cell cycle progression by decreasing cyclin B and Cdk2 proteins [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have determined the mechanisms underlying the inhibitory effect of C-PC isolated from various rich sources on the growth of different cancer cells. Mainly, cell cycle arrest, induction of apoptosis, induction of autophagic cell death, inhibition of DNA replication, and generation of reactive oxygen species (ROS) were reported among the underlying mechanisms [11,[48][49][50]. However, further clarification of the molecular mechanisms underlying the effect of C-PC on cancer as well as normal cells is mandatory in order to develop an effective strategy and to direct its clinical application [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed to the role of C-PC as an antioxidant, anti-cancer, neuroprotective, immunomodulatory, anti-inflammatory agent, as well as a non-toxic photosensitizer in tumour treatment [5][6][7]. The importance of pure C-PC resides in its anti-proliferative and pro-apoptotic effects on different types of cancer cell lines [8][9][10][11], where there are no recorded side effects on normal cells [5,12]. For this reason, the purity of C-PC is considered the main challenge among researchers [3,13].…”
Section: Introductionmentioning
confidence: 99%